Dermal penetration and resorption of beta-naphthylamine and N-phenyl-beta-naphthylamine from lubricants in an ex vivo human skin model - Dennerlein, Kathrin; Göen, Thomas; Zobel, Melanie; Boos, Anja; Drexler, Hans; Kilo, Sonja (Chemosphere, 2017)
Dermal Penetration of aromatic amines (AA's), often suspected or known to be carcinogenic, can play an important role in the overall human exposure. However, information on penetration of certain AA's is poor and inconsistent. Penetration of the former lubricant additive N-phenyl-beta-naphthylamine (PBNA) and its contaminant beta-naphthylamine (BNA) a known carcinogen was investigated and the influence of formulation and co-application characterized. Percutaneous penetration of BNA and PBNA through freshly excised human skin (n = 8; 48 h) was investigated using an ex vivo diffusion cell model. Both AA's were applied in a technical-conform lubricant or dissolved in hexane. The amount of BNA and PBNA applied to skin was 0.52 and 259 ?g/0.64 cm2. The analytical determination of AA's was performed by GC-MS. Both, BNA and PBNA penetrated through human skin (38 vs. 5% of applied dose). In contrast to BNA, the percutaneous penetration of PBNA continued beyond the end of exposure. Co-exposure of both AA's increased the intradermal uptake of BNA and PBNA (p < 0.05). Exposure in lubricant showed the least overall penetration (2.9 and 1.9% of applied dose). The results clearly reveal that dermal penetration of both AA's depends strongly on the mode of application. Co-application and formulation alters the penetration of the AA's.
EVALuna2:9769

LC-MS/MS procedure for the simultaneous determination of N-acetyl-S-(1-naphthyl)cysteine and N-acetyl-S-(2-napthyl)cysteine in human urine - Zobel, Melanie; Klotz, Katrin; Göen, Thomas (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2018)
A two-dimensional liquid chromatographic electrospray-ionization tandem mass spectrometric (LC/LC-ESI-MS/MS) procedure for the simultaneous determination of the expected mercapturic acids of naphthalene (1- and 2-naphthylmercapturic acids; 1- and 2-NpMA) and of the well-established parameter for benzene biomonitoring (S-phenylmercapturic acid; PhMA) in human urine was developed, validated and applied to human urine samples. Apart from sample acidification, the enrichment of analytes and sample clean-up as well as the separation of all analytes were completely automated using both a restricted access material column (RAM C18) and a core-shell biphenyl material. Sensitive, specific and reliable detection of all target substances, with limits of detection ranging from 0.03 to 0.04 μg/L, was achieved using structurally well matching isotope-labelled internal standard substances for each analyte. Intraday and interday precision were determined, ranging from 2.2 to 4.3%, and mean accuracy from 98.4 to 100.8%. Due to the low limits of detection, the good precision and accuracy of the developed procedure, it is well suited for application in biomonitoring studies to evaluate the validity of mercapturic acids as biomarkers after naphthalene exposure.
EVALuna2:33781

Reliable quantification of 1,2-dihydroxynaphthalene in urine using a conjugated reference compound for calibration - Zobel, Melanie; Göen, Thomas; Belov, Vladimir; Klotz, Katrin (Analytical and Bioanalytical Chemistry, 2017)
After environmental and occupational exposure to naphthalene, 1,2-dihydroxynaphthalene (1,2-DHN) was shown to be one major metabolite in human naphthalene metabolism. However, the instability of free 1,2-DHN complicates the reliable determination of this promising biomarker in urine. To solve this stability problem, glucuronide conjugates of 1,2-DHN and the corresponding isotopically labelled D6-1,2-dihydroxynaphthalene (D6-1,2-DHN) were synthesised and applied as reference material and internal standard in a gas chromatographic-tandem mass spectrometric (GC-MS/MS) method. The determination of 1- and 2-naphthol (1-MHN, 2-MHN) was included in the procedure to enable a comprehensive assessment of naphthalene metabolism and exposure. The results of the validation showed a high reliability and sensitivity of the method. The detection limits range from 0.05 to 0.16 ?g/L. Precision and repeatability were determined to range from 1.4 to 6.6% for all parameters. The simultaneous determination of 1- and 2-MHN as additional parameters besides 1,2-DHN enables the application of the method for further metabolism and kinetic studies on naphthalene. The use of glucuronide-derivative reference substances and the application of structurally matched isotopic-labelled internal standards for each substance guarantee a reliable quantification of the main naphthalene metabolites 1,2-DHN and 1- and 2-MHN. Graphical abstract Reliable quantification of 1,2-dihydroxynaphthalene in urine using a conjugated reference compound for calibration.
EVALuna2:9768

Suitability of several naphthalene metabolites for their application in biomonitoring studies - Klotz, Katrin; Zobel, Melanie; Schäferhenrich, Anja; Hebisch, Ralph; Drexler, Hans; Göen, Thomas (Toxicology Letters, 2018)
Naphthalene occurs together with polycyclic aromatic hydrocarbons (PAHs) at industrial workplaces and is ubiquitous in the environment. For biological monitoring of naphthalene exposures, up to now mainly 1- and 2-naphthol in urine have been used. Recently, we proposed 1,2-dihydroxynaphthalene (1,2-DHN) and the 1- and 2-naphthylmercapturic acid (1- and 2-NMA) as new urinary biomarkers to characterise a naphthalene exposure. In this study, in a collective of nine occupationally exposed workers handling with creosote the naphthalene metabolites 1,2-DHN, 1- and 2-NMA as well as 1- and 2-naphthol were analysed in order to evaluate the suitability of the different parameters for their application in biomonitoring studies. Additionally, air sampling was conducted to characterise the exposure in task related exposure situations at different workplaces. In the analysed 51 urine samples, 1,2-DHN was the main metabolite with concentrations ranging from 2.3 to 886 μg/g creatinine (crea) (median 34 μg/g crea). For the sum of 1- and 2-naphthol, concentrations in the range of 2.6-174 μg/g crea (median 15 μg/g crea) were observed. 1-NMA concentrations were in the range of < LOD-2.4 μg/g crea (61% > LOD), while 2-NMA was not detected in the analysed urine samples. The biomarkers 1,2-DHN, 1- and 2-naphthol as well as 1-NMA showed significant correlations, which pointed out to naphthalene as the common exposure source. The poor correlations between naphthalene in the air and the biomarkers in urine may be a result of the varying exposure situations and may indicate not solely inhalative, but additional dermal uptake. 1,2-DHN was the most sensitive and, together with 1-NMA, the most specific parameter of the biological monitoring of naphthalene exposure at workplaces. Further studies with this parameter are needed for individuals at different workplaces as well as for persons of the general population without occupational PAH exposure to characterise 1,2-DHN levels as well as to establish their relationship with the naphthalene exposure.
EVALuna2:35248

Validity of different biomonitoring parameters in human urine for the assessment of occupational exposure to naphthalene - Klotz, Katrin; Weiß, Tobias; Zobel, Melanie; Bury, Daniel; Breuer, Dietmar; Werner, Silke; Sucker, Kirsten; Zschiesche, Wolfgang; Göen, Thomas; Brüning, Thomas; Drexler, Hans (Archives of Toxicology, 2019)
Up to date, information on the validity of human biomonitoring (HBM) parameters of naphthalene exposure is poor. This study was performed to reveal the relation between occupational exposure to naphthalene and biological exposure markers. Therefore, ten lowly and highly exposed workers from the abrasives industry were selected to characterise a broad exposure range. Naphthalene in air was determined by personal air monitoring during one shift. For biological monitoring, pre- and post-shift urine samples collected on 2 days of a working week were analysed for 1,2-dihydroxynaphthalene (1,2-DHN), 1- and 2-naphthol, 1- and 2-naphthylmercapturic acid (NMA). The naphthalene concentration in air was in the range of 0.5 to 11.6 mg/m3. The biomarkers in urine showed post-shift concentration in the range of 114–51,809 µg/L for 1,2-DHN, 0.8–666 µg/L for 1–NMA, 2–2698 µg/L for 1-naphthol and 4–1135 µg/L for 2-naphthol, respectively. 2-NMA was not detected. The urinary levels increased significantly from pre- to post-shift for all analysed parameters and an accumulation over the working week was observed. Significant positive correlations were observed between 1,2-DHN, 1-NMA, 1- and 2-naphthol in post-shift urine samples and personal exposure to naphthalene in the air. 1-NMA and 1,2-DHN, 1- and 2-naphthol have been demonstrated as suitable biomarkers for naphthalene exposure monitoring. Of the determined biomarkers, 1,2-DHN is by far the metabolite with the highest concentration in the urine samples.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Biomonitoring; Dihydroxynaphthalene; Mercapturic acid; Naphthalene; Naphthol; Urine